From e-commerce to v-commerce: an empirical study on consumers acceptance in Brazil - Figliozzi, Erica (2018)
Although Virtual Reality (VR) is considered to be one of the new technologies with the highest potentiality, especially in the retail field, research into customers’ acceptance and intentions to use this technology is currently limited. This study investigates the variables that can influence the degree of intention to use VR along the purchasing process and it has been conducted in the Brazilian market. In particular, the tested variables are: effort (of purchasing and of using the technology), enjoyment, and convenience. Moreover, it has been taken into account the possible moderator role of the Need for Touch (NFT). Data have been collected mainly through a survey. Results have shown that enjoyment, convenience and purchasing effort are statistically significant. However, there is no evidence for the effect of the perceived effort/easiness to use the technology and neither for the mediating effect of the NFT. The value of this research is that it shows what the factors and the obstacles are that can affect the use of VR for shopping.